Muslim Parental Involvement in Indonesian Islamic Primary Schools: Gendered Caregiving, Religious Responsibility, and Uneven School Participation - Faoziah, Niswatin (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – Current parental involvement research remains largely shaped by school-centred frameworks that give greater visibility to institutionally recognised forms of participation than to home-based educational labour. This study examines how Muslim parents in Indonesian Islamic primary schools understand and enact parental involvement, with particular attention to religious responsibility, gendered caregiving, and participation in school-based structures. Design/methods/approach – The study uses an interpretive qualitative multiple-case design based on in-depth interviews with 10 Muslim parents, comprising 6 mothers and 4 fathers, whose children attend a public madrasah ibtidaiyah, a private madrasah ibtidaiyah, and an integrated Islamic primary school in Yogyakarta, Indonesia. Participants were selected purposively to capture varied parental experiences across different Islamic schooling contexts. Data were analysed thematically to identify recurring patterns in how parental roles, caregiving practices, and relations with school authority were understood and negotiated.Findings – The findings indicate that parental involvement was understood primarily as a religious and moral responsibility enacted through home-based educational labour, including academic support, character formation, and religious guidance. These responsibilities were strongly gendered, with mothers assuming the main role in children’s everyday educational care. Parents’ participation in formal school decision-making remained limited and largely consultative, but this did not necessarily indicate disengagement. Rather, much of their educational involvement took place outside school-recognised forms of participation. Research implications/limitations – Based on a small qualitative sample, the study offers a contextualised rather than generalisable account of Muslim parental involvement. Its findings suggest that parental involvement frameworks need more critical examination in global educational research, especially in Muslim societies and other culturally grounded, underrepresented settings where educational responsibility extends beyond school-recognised participation.Practical implications – The findings suggest that school leaders and teachers need more inclusive ways of recognising home-based caregiving as part of parental involvement, while also creating clearer and more meaningful avenues for parental participation in school life.Originality/value – This study provides contextual evidence from Indonesian Islamic primary schools, highlighting the limits of school-centred models in capturing religious, gendered, and home-based parental involvement. It contributes to global educational theory by supporting the pluralisation of parental involvement research, particularly by foregrounding Muslim societies, the Global South, and other underrepresented contexts.Paper type Research paper